Thismia andicola sp. nov. (Thismiaceae): a new species from the northern Andes in Colombia - Aguilar-Cano, José; Guzmán-Guzmán, Santiago; Lopera-Toro, Alejandro (Phytotaxa, 2023)
Knowledge on the mycoheterotrophic genus Thismia (Thismiaceae) in the neotropics is scarce, where the majority of species are known from Brazil, with 13 currently accepted species, of which seven are endemics. All the 15 known species of the genus in the Americas, except T. americana, inhabit forests below 1300 m a.s.l. Two species of Thismia are known from Colombia, T. panamensis from the Chocó biogeographical region and T. glaziovii from the Amazonian region. Here we describe a third Colombian species, T. andicola sp. nov. distinguished by having outer surface of the floral tube light blue and densely punctate with sky-blue metallic dots, inner tepals 4.6–5 mm long and stigma obovoid, covered adaxially by regularly distributed simple uniseriate multicellular trichomes. It is collected in the buffer zone of the Tamá National Park, Norte de Santander and is the first species of Thismia recorded from the Andes, and the first American species found above 2000 m a.s.l. We provide a description, drawings, photographs, distribution map, and the provisional conservation status of the new species. A key to species of Thismia sect. Ophiomeris species is also included.